Outcomes of humeral osteotomies versus soft-tissue procedures in secondary surgical procedures for neonatal brachial plexus palsy: a meta-analysis - Azer, Amanda; Mendiratta, Dhruv; Saad, Anthony; Duan, Yajie; Cedarstrand, Matthew; Chinta, Sree; Hanna, Aedan; Shihora, Dhvani; McGrath, Aleksandra; Chu, Alice (Frontiers in Surgery, 2023)
Secondary surgical procedures can be used in brachial plexus birth injury to correct shoulder movement imbalances. This study compares outcomes of the two secondary surgical procedure types: humeral osteotomies and soft tissue procedures. Outcome measures assessed included active and passive internal and external rotation, active and passive abduction and adduction, active and passive flexion and extension, percentage of the humeral head anterior to the middle glenoid fossa, glenoid version, and Mallet Score. Nineteen full-text articles were included in the analysis. Humeral osteotomies resulted in a loss of internal rotation postoperatively (-15.94°).Active internal rotation was not evaluated for soft tissue procedures. All other assessed outcomes were improved postoperatively for bony and soft tissue procedures. Bony procedures exhibited a greater degree of active external rotation postoperatively when compared to soft tissue procedures (+67° vs +40°). Both bony and soft tissue procedures Improve shoulder function in children with neonatal brachial plexus palsy, however, soft tissue procedures showed greater consistency in outcomes.